The Effect of Distributive, Procedural, and Interactional Justice on Organizational Cynicism Moderated by Hope - Narosaputra, Dewo Agung Nugroho; Pangestu, I Ketut; Sengkey, Marssel Michael (Faculty of Psychology, Universitas Gadjah Mada, 2023)
Theoretical and empirical evidence suggests that organizational justice impacts organizational cynicism, but the influence of its various dimensions is inconsistent. This inconsistency necessitates the introduction of moderating variables for a more comprehensive understanding. In this context, hope is selected as a moderating variable due to its ability to mitigate the adverse effects of organizational cynicism. The objective of this study is to explore how distributive, procedural, and interactional justice affect organizational cynicism, with hope serving as a moderating factor. The research adopts an explanatory correlational design. Participants include 126 employees from the Mojokerto State Police School (SPN), selected through census sampling. The study utilizes scales for measuring organizational cynicism, organizational justice, and hope. Data is analyzed using moderated regression analysis (MRA). The findings reveal that distributive and interactional justice negatively impact organizational cynicism. Moreover, hope moderates the relationship between procedural justice and organizational cynicism, as well as the impact of interactional justice on cynicism. Significantly, hope moderates the effects of distributive, procedural, and interactional justice on organizational cynicism, underscoring its role in enhancing the impact of these justice dimensions on cynicism. This research contributes to a nuanced understanding of the interplay between organizational justice and cynicism, highlighting the critical role of hope as a moderator.